(untitled) (Research, Society and Development, 2020)
In order to provide subsidies for making seedlings of forest species, it is essential to have knowledge of the germinative process of seeds that have the impermeable coat. In view of this, the objective was to evaluate methods of overcoming dormancy alternative to sulfuric acid for seeds of Enterolobium contortisiliquum (tamboril). A completely randomized design with eight treatments and four replications was used. Dormancy overcoming treatments were used: control, chemical scarification using sulfuric acid for 20 minutes, chemical scarification with Thinner for 3; 4; 5; 6 and 7 hours and mechanical scarification with sandpaper number 80 on the opposite side to the micropyle. The characteristics evaluated were: emergence, speed index and mean time of emergence, aerial part, root, dry matter mass of the aerial part, of the root system. The use of Thinner was efficient to promote the dormancy of E. contortisiliquum seeds, however they present low germination when compared to sulfuric acid treatments or scarification with iron sandpaper, being necessary to submit the seeds for a period superior to 7 hours for promote greater germination.